Ammo Acid Profile and Anti-Hypertensive Activity of Collybia reinakeana P. Henn - Reyes, Renato G. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2010)
The amino acid profile and the inhibitory activity of the angiotensin-converting enzyme (ACE) of Collybia reinakeana P. Henn. were elucidated in our attempt to provide benchmark data regarding its use in the mushroom-based nutraceutical industry. C. reinakeana produced a colony of relatively big and heavy fruiting bodies with a cumulative weight of 5, 965 g. The length of its stipe ranged from 20-200 mm and the diameter of its pileus from 7-136 mm. The stipe contained essential amino acids, namely, phenylalanine >threonine >lysine >valine >leucine > isoleucine>tryptophan and methionine, in decreasing order of abundance. Similarly, phenylalanine was the most abundant in the pileus followed by lysine> threonine>valine> leucine>isoleucine>tryptophan and methionine. Aside from these essential amino acids, glutamine and glutamic acid were also noted both in the pileus and the stipe, which make C. reinakeana an excellent culinary ingredient. The two most important non-standard amino acids in the nutraceutical industry, ornithine and γ-aminobutyric acid (GABA), were also detected. C. reinakeana exhibited anti-hypertensive activity as demonstrated in the ability of its hot water extract to inhibit angiotensin-converting enzyme. Toxicity test in Crlj:CD1 (ICR) mice confirmed that it is an edible mushroom.